Kinetics Model of Tomato Quality Changes During Storage - Masithoh, Rudiati Evi; Rahardjo, Budi; Sutiarso, Lilik; Harjoko, Agus (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
This study aims at developing a kinetics model of changes in tomatoes quality during storage. Samples were stored at temperature of 6, 15, and 28 °C. Quality parameters measured were total carotene, citric acid, and vitamin C. On the development of kinetic models of quality parameter changes the k values of total carotenoids, citric acid, and vitamin C were 0.075, -0.008, and 0.042 at 6 °C, 0.056, -0.029, and 0.049 at 28 °C, as well as 0.125, -0.039, dan 0.044 at 28 °C, respectively. Activation energy of the decrease of citric acid was 47.91 kJ/mol, whereas for total carotene and vitamin C were 17.83 kJ/mol dan 0.96 kJ/mol. The coefficient of determination (R2) of the quality content between observation and prediction were 0.70-0.96. Keywords: Kinetics, total carotene, citric acid, vitamin C, tomato